2021
DOI: 10.7759/cureus.13308
|View full text |Cite
|
Sign up to set email alerts
|

McKittrick-Wheelock Syndrome: A Rare Cause of Chronic Diarrhea

Abstract: Diarrhea is the principal cause of the majority of healthcare utilization. When diarrhea lasts longer than four weeks, it is considered chronic diarrhea. There are several causes of chronic diarrhea, but here we focus on one of the rare causes, known as McKittrick-Wheelock syndrome (MWS). We here present the case of a patient in his seventies with chronic diarrhea, found to have tubulovillous adenoma and diagnosed with McKittrick-Wheelock syndrome. We also discuss the clinical presentation, pathophysiology, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Recently published studies have shown an increase in the usage of minimally invasive procedures such as transanal endoscopic microsurgery, transanal minimally invasive surgery, endoscopic mucosal resection, and endoscopic submucosal dissection [ 21 , 22 ]. However, some authors noticed that the risk of recurrence is greater after minimally invasive operations [ 4 , 9 , 18 ]. Endoscopic techniques may be technically challenging due to the large size of the tumor in MWS patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently published studies have shown an increase in the usage of minimally invasive procedures such as transanal endoscopic microsurgery, transanal minimally invasive surgery, endoscopic mucosal resection, and endoscopic submucosal dissection [ 21 , 22 ]. However, some authors noticed that the risk of recurrence is greater after minimally invasive operations [ 4 , 9 , 18 ]. Endoscopic techniques may be technically challenging due to the large size of the tumor in MWS patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The largest systematic study revealed a long duration of symptoms and severe electrolyte imbalances for patients with MWS [ 8 ]. However, the real prevalence of MWS in combination with colon adenoma is unknown [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As tumor size increases, enteral losses worsen, thus overloading compensation mechanisms. 11,31 Hypersecretory villous adenomas are capable of generating notable hydroelectrolytic disturbances, as these tumors can cause a rectal loss of 4 liters a day, containing on average 120 mmol per liter of sodium, 4.4 mmol per liter of potassium and 123 mmol per liter chloride. At first, there is the possibility of balancing the deficit of electrolytes and fluids through greater oral intake and renal adaptation.…”
Section: 192428mentioning
confidence: 99%
“…Subsequently, it is crucial to remove the tumor through surgery or endoscopy, which is the basis of treatment. 2,3,11,30,31 One study showed that patients who underwent endoscopic resection occasionally required further resection surgery or additional endoscopic techniques to achieve total resection. It was notable that, according to the tumor dimensions, there was an increase in the technical complexity of the endoscopic approach.…”
Section: 192428mentioning
confidence: 99%
See 1 more Smart Citation